Compulsory Licensing
VI, 458 p. 2 illus.
Keywords: Under the auspices of the Max Planck Institute for Intellectual Property and Competition Law (now the Max Planck Institute for Innovation and Competition). and Institutum Iurisprudentiae, Academia Sinica, a group of twenty scholars from around the world gathered to study the experiences made with regards to compulsory licensing. The results are demonstrated in this book. Different articles analyze how the international conventions on intellectual property may be interpreted and explore the related doctrinal groundwork surrounding compulsory patent licensing and beyond. It is shown how the compulsory licensing regime could be transformed into a truly workable mechanism facilitating the speedy use and dissemination of innovation and other subject matters of protection.